Water Pollution in Coastal Communities in Indonesian: A Review - Siti Nurfadilah H; Nurmiaty Hamzah; Widarni (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Water pollution in coastal areas poses both direct and indirect threats to public health. Exposure to contaminated water can lead to various illnesses, including gastrointestinal disorders, dermatological infections, and respiratory diseases resulting from the inhalation of toxic gases or pollutant particles. Moreover, the consumption of fish or seafood contaminated with hazardous substances may result in the bioaccumulation of toxic elements in the human body, increasing the risk of chronic conditions such as liver damage, kidney dysfunction, and neurological disorders. Objectives: This study aims to explore the relationship between coastal water pollution and public health outcomes in order to support the development of more effective policies and strategies for sustainable coastal environmental management. Method: This research is a literature review intended to identify and synthesize findings from relevant national and international journal articles. Literature sources were retrieved using Google Scholar, employing keywords such as